Green human resource management practices as a factor developing employees’ green behaviour - Mert Aksakal, Omer; Šarkiūnaitė, Ingrida; Ščiukauskė, Indrė (Transformations In Business & Economics, 2026)
Linking environmental sustainability with HRM leads to the reorganization of traditional HRM practices. Practices can also be used for improved environmental performance by shaping individual behaviours. The aim of the article is to investigate the influence of green human resource management practices on employee green behaviour. Theoretical and analytical analysis reveals that green behaviours of employees make HRM environmentally effective, employees prefer environmentally responsible employers, and for organizations, recruiting environmentally aware candidates is more effective, and a green reputation can bring a competitive advantage. The research showed that recruitment and selection do not influence employee green behaviour. It is essential that a two-step GHRM adoption plan for organizations is offered as follows: (1) includes employee empowerment, performance management, appraisal, training, and development (should be given priority while implementing GHRM); (2) includes rewards, and management commitment. It can provide a better understanding for organizations regarding the implementation of GHRM practices and encouraging green behaviours.